Peran Ekonomi Makro dan Mikro di Indonesia - Muchamat Amarodin (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
National economic problem is the scope of the macro economy. A country in order to develop their economy will surely meet some obstacles. Barriers it was an internal matter to be resolved by the state government of the country. Barriers that such uncontrolled inflation and unemployment problems that can not be separated from issues of quality and quantity of the population in Indonesia is very diverse. In resolving the problem, surely a country to apply its policy as the holder of autonomy. The policy was successful or not is an end that should be fought.